2015
DOI: 10.1016/j.jcv.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus seroprevalence in the general female population from 8 countries

Abstract: Background Hepatitis C virus (HCV) infection is a significant global health issue because it is widespread and persistent and can cause serious liver diseases. Objectives The aim of this study is to estimate HCV prevalence in women from the general population in different geographical areas worldwide and to assess the potential role of sexual behaviour in the virus transmission. Study design Each participating centre recruited a random sample of women from the general population aged from less than 20 to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
0
7
0
2
Order By: Relevance
“…Twenty one percent (9/42) of the publications reported data from Ho Chi Minh City (HCMC) or from the southern Vietnam region (Table 1 ), while 52.3% (22/42) reported studies conducted in the north of the country, principally in Hanoi and surrounding provinces [ 18 , 22 , 27 , 32 , 36 , 47 , 49 , 52 , 53 ] (Table 1 ). Eight of forty two retrieved publications characterized the diversity of HCV genotypes in Vietnam [ 14 , 16 , 21 , 33 , 34 , 48 , 50 , 51 ] (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty one percent (9/42) of the publications reported data from Ho Chi Minh City (HCMC) or from the southern Vietnam region (Table 1 ), while 52.3% (22/42) reported studies conducted in the north of the country, principally in Hanoi and surrounding provinces [ 18 , 22 , 27 , 32 , 36 , 47 , 49 , 52 , 53 ] (Table 1 ). Eight of forty two retrieved publications characterized the diversity of HCV genotypes in Vietnam [ 14 , 16 , 21 , 33 , 34 , 48 , 50 , 51 ] (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our search identified that HCV seroprevalence in the population may be high (1–4%) compared to other countries in the region [3, 27, 53]. For example, several large-scale seroprevalence studies have reported HCV estimates of asymptomatic Chinese ranging from 0.39 to 3.2% depending of the region [65].…”
Section: Ascertaining the Burden Of Hepatitis C In Vietnammentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of CHC infection in the general population was 1.4%–4.2% in 1994–2005, 2.15% in 2004, 2.2% in 2005–2008, and 0.97% in 2014, according to the 2014 national survey [ 12 , 27 , 28 ]. Susceptible populations were persons with unsafe injection practices, inadequate sterilization of medical equipment in health care settings, and unscreened blood products.…”
Section: Methodsmentioning
confidence: 99%